Kesiapan Pekerja Dalam Protokol Kesehatan di Tatanan Baru Era Pandemi Covid-19 Di Hotel XX - Kohar Sulistyadi; Zallerene Anggiet; M. Tomy Haryanto; P. U. Pandi; R. M Pasaribu (Universitas Sahid Surakarta, 2021)
n protecting workers from the corona virus: COVID-19, the employment preparedness for preventive action must be carried out in accordance with health protocol. Preventive efforts are best practices to reduce the impact of COVID-19 at XX Hotels. Hotel XX has conducted a feasibility evaluation of the health protocol for the employment preparedness. This protocol aims to handle the prevention of Covid-19, especially for workers, guests and stakeholders. While the vaccine has not been given to the public/workers, the prevention of positive cases of Covid-19 expects all parties to implement the health protocol. The health protocol assessment results in XX Hotel show that the assessment achievement was 97% above the minimum 90%. Therefore, workers can be feasible to work according to the implementation of the health protocol and work with WFO (work from the office) in a new normal and get a certificate of eligibility for the health protocol.